Vocational School Curriculum Development Design in the Era of the 4.0 Industry Revolution - Nurima sari; Supadi Supadi; Siti Zulaikha (STAI Miftahul Ula Nganjuk, 2020)
This study aims to determine the design of SMK curriculum development in the era of the Industrial Revolution 4.0. This study uses a qualitative research type method, namely the Literature Study. Data collection is sourced from several theories obtained from secondary data, namely journal articles, the internet, and books. The results of the literature study show that in the design of vocational curriculum development in the Industrial Revolution Era 4.0, it is necessary to form a monitoring and evaluation team, be literate in technology, use learning designs, and improve 21st-century skills such as critical thinking and problem-solving; communication and collaboration; creativity and innovation; and engagement with industry partners.